PROBLEMS AND DIRECTIONS OF THE COMPETITIVENESS OF GRAIN PRODUCERS IMPROVING - В. С. Ніценко; І. А. Дворніков (Ринкова економіка: сучасна теорія і практика управління, 2016)
The subject of research is theoretical and practical approaches of grain production in Ukrainian agricultural enterprises, problems and ways of its improvement raising. Purpose of the article is an analysis of the current state of grain production and determining the level of competitiveness of agricultural enterprises in the regions and between countries, the main problems hampering the development of grain production and processing of ways to improve the competitiveness of grain. The author used the following methods: comparison – to determine the actual level of biological productivity and between countries; analysis – to identify trends in grain production; monographic – to study advanced experience of domestic enterprises – producers of grain; abstract logical – for theoretical generalizations and drawing conclusions. The result of the research is the main problems identifying that hinder the growth and yield of crops, grain production’s basic strategic principles formulating. Areas of application results: materials research can be used by scientists and specialists to address improving the competitiveness of grain production in agriculture. The most problematic issues, which hamper the competitiveness of farms grain sector, are the lack of funds for maintenance operations, curtailment of state and regional funding programs of agricultural production, including grain, high rates of bank loans monopoly mediation and processing facilities for grain, resulting in part of the loop manufacturing operations, the inability to buy seeds of high reproductions (zoned) crops, no performance standards of mineral fertilizers and plant protection, low use genetic and biological potential of crops. The main directions of the grain competitiveness improving is the introduction of intensive production technologies, including minimum and zero tillage, integrated structures forming or joining them, introducing a mechanism pledge and intervention purchases of grain and so on.